2017
DOI: 10.3171/2016.7.jns16460
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative auditory steady-state monitoring during surgery in the cerebellopontine angle for estimation of postoperative hearing classes

Abstract: OBJECTIVE Brainstem auditory evoked potentials (BAEPs) have been used for intraoperative monitoring of the auditory nerve for many years. However, BAEPs yield limited information about the expected postoperative hearing quality and speech perception. The auditory steady-state response (ASSR) enables objective audiograms to be obtained in patients under anesthesia. These ASSRs could be used for intraoperative estimation of hearing classes to improve the postoperative outcome and quality of life. Studies investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Brainstem auditor y evoked potentials are an important tool for maintaining the vestibulocochlear nerve function. All patients shall undergo audiometry for pre-and postoperative assessment of the auditory analyzer condition [14].…”
Section: Discussionmentioning
confidence: 99%
“…Brainstem auditor y evoked potentials are an important tool for maintaining the vestibulocochlear nerve function. All patients shall undergo audiometry for pre-and postoperative assessment of the auditory analyzer condition [14].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported the utility of auditory steady-state responses for intraoperative monitoring. 12,13 Cortico-cortical evoked potentials have also been applied for intraoperative monitoring to preserve language function. 16,17 The present results indicate that SSCCEPs may replace conventional CCEPs for more convenient intraoperative monitoring; however, further studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…4 Because the responses to these periodic stimuli have a stable amplitude and phase over time, they are termed steady-state evoked potentials. Steady-state evoked potentials have been used in visual evoked potentials, [4][5][6][7][8][9] auditory evoked potentials, 3,[10][11][12][13] and sensory evoked potentials. 14,15 "Cortico-cortical evoked potential" (CCEP) is a technique for tracing in vivo brain tracts.…”
mentioning
confidence: 99%
“…Second, further SDS tests and long-term hearing evaluations would be more helpful for evaluating hearing function. Finally, considering the delay effect of averaged BAEPs, better monitoring patterns [8] and methods [11,13,18] with faster acquisition [8] of valuable indicators are still required.…”
Section: Discussionmentioning
confidence: 99%